ESG Transparency on the Polish Capital Market - Sroka, Robert (Annales. Etyka w Życiu Gospodarczym, 2018)
The article presents the results of five years of research on transparency levels regarding the disclosure non‑financial data by companies listed on the Warsaw Stock Exchange (WSE). The research was conducted as part of a project entitled “ESG analysis of companies in Poland”. The goal of the project is to provide credible knowledge about the quality of environmental, social and corporate governance (ESG) data on the Polish capital market. The article mainly contains the results of a comprehensive analysis of how well the listed companies reported ESG related data in 2016. The five years of analysis enable us to show a change in the level of non‑financial data disclosure between 2012 and 2016.1 The results of the research show that, from an investor’s perspective, there is still a huge information gap on the Polish capital market, especially in the reporting of environmental and social data.